Spectroscopic, optical, electronic and NLO characteristics of long chain tosyloxy based chalcone derivative: a quantum chemical approach - Vinay Parol; K. S. Pavithra; G. H. Pujar; Santhosh Kumar M. V; M. R. Jagadeesh (Discover Chemistry)
Abstract This study presents a comprehensive computational investigation of “4- [(1E)-3-(4-chlorophenyl)-3-oxoprop-1-en-1-yl]phenyl 4-methyl benzene-1-sulfonate” (COP) molecule. Key parameters explored include the geometric optimized structure, spectroscopic, vibrational modes, natural bond orbital (NBO) analysis, nonlinear optical (NLO) properties and other molecular characteristics. 1H-NMR was generated using a gauge-invariant atomic orbital approach, and strong agreement was shown with those determined experimentally. The vibration modes were obtained experimentally and compared theoretically. The quantum chemical calculations for COP were carried out using density functional theory (DFT) with the B3LYP functional and the 6–31 + G(d, p) basis set. Using TD-DFT, the absorption spectrum of COP was simulated for various solvents and chemical reactivity parameters were computed using the highest occupied molecular orbital (HOMO) – lowest unoccupied molecular orbital (LUMO) values. The energy gap (experimentally) obtained agrees with the HOMO-LUMO energy gap. Electrostatic mapping was done on the COP molecule to understand the electrostatic charge distribution in the molecule. The values for polarizability and hyperpolarizability (first and second order) were obtained as nonlinear optical parameters at static and dynamic frequencies, measured at 0.08564, 0.05695, 0.05062, and 0.04282 a.u. The second-order hyperpolarizability ( $$\:γ\:$$ ) (6928.012 × 10−36 esu at $$\:{\upomega\:}=0.08564\:\text{a}.\text{u})$$ , is found to be 40 folds greater than the static field ( $$\:γ\:=\:166.9\:×\:\:{10}^{-36}\:\text{e}\text{s}\text{u}\:\text{a}\text{t}\:{\upomega\:}=0.0\:\text{a}.\text{u})$$ . The results show that COP molecule is a promising material for NLO applications.